Acute kidney injury post‐heart transplant: An analysis of peri‐operative risk factors. Issue 6 (8th April 2021) - Jocher, Brandon M.; Schilling, Joel D.; Fischer, Irene; Nakajima, Tomohiro; Wan, Fei; Tanaka, Yuki; Ewald, Gregory A.; Kutkar, Kunal; Masood, Muhammad; Itoh, Akinobu
Abstract: Acute kidney injury is a common complication following heart transplantation, and the factors contributing to acute kidney injury are not well understood. We conducted a retrospective cohort study evaluating patients who underwent heart transplantation between 2009 and 2016 at a single institution. The primary endpoint was incidence of acute kidney injury as defined by Kidney Disease Improving Global Outcomes criteria. Secondary endpoints included 30‐day hospital readmission, 30‐day mortality, and 1‐year mortality. A total of 228 heart transplant patients were included in the study for analysis. In total, 145 (64%) developed acute kidney injury, where 43 (30%) were classified as stage I, 28 (19%) as stage II, and 74 (51%) as stage III. Risk factors found to be associated with the presence of acute kidney injury included increased use of vasopressors and inotropes post‐transplant. Protective factors included cardiopulmonary bypass time <170 min. Acute kidney injury was found to be associated with increased 30‐day and 1‐year mortality.